IMPLEMENTASI PROBLEM BASED LEARNING, PROJECT BASED LEARNING, DAN DISCOVERY LEARNING DALAM PEMBELAJARAN MATEMATIKA UNTUK MENINGKATKAN KEAKTIFAN BELAJAR SISWA KELAS V SEKOLAH DASAR - Shalsya Nazyfha; Ananta Lestari Br Sembiring; Berta Arista Br Damanik; Mutiara Uli Arta Tambunan; Liza Aulia Yusuf (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Low student participation and the belief that mathematics is a challenging and abstract topic are two common obstacles to mathematics education in elementary schools. The purpose of this study is to describe how Problem-Based Learning (PBL), Project-Based Learning (PjBL), and Discovery Learning are used in mathematics instruction and how they improve fifth-grade students' learning activity. A qualitative descriptive strategy was used in this study. Data reduction, data display, and conclusion drawing approaches were used in the analysis of the information gathered from interviews with the fifth-grade teacher at SD Negeri 101774 Sampali. The results demonstrated that students were more engaged in the learning process when these student-centered learning approaches were used. Pupils showed improved critical thinking abilities when resolving contextual issues, grew more comfortable voicing their viewpoints, and engaged in group discussions. Students' comprehension of abstract mathematical ideas was further aided by the use of educational videos, workbooks, and teaching aids. The findings show that PBL, PjBL, and discovery learning successfully promoted a more engaging and relevant mathematics learning environment, despite issues such as constrained instructional time and uneven student involvement.